The Influence of Foreign Direct Investment, Small and Medium Micro Enterprises on Economic Growth and Its Impact on Reducing Unemployment in DKI Jakarta Province - Susanti, Ria Johan; Supandi, Agus; Margiyanto Adi, Tony (PT. Maju Malaqbi Makkarana, 2024)
This study examines the influence of Foreign Direct Investment (FDI) and Micro, Small, and Medium Enterprises (MSMEs) on economic growth and its impact on unemployment reduction in the Province of DKI Jakarta. The analysis reveals a significant positive correlation between FDI and economic growth, highlighting the role of foreign capital, technology transfer, and managerial expertise in boosting regional productivity. Similarly, MSMEs contribute significantly to the Gross Regional Domestic Product (GRDP) and employment creation, supported by government policies facilitating access to finance, training, and business support. The study also finds that economic growth driven by FDI and MSMEs effectively reduces unemployment rates. Recommendations for policymakers include creating a favorable investment climate, strengthening MSME support, ensuring inclusive economic growth, and enhancing public-private collaboration. These measures aim to sustain the positive impact of FDI and MSMEs on economic development and job creation in DKI Jakarta.